The (totally not) guaranteed guide to popularity, prettiness & perfection - McCafferty, Megan (McCafferty, Megan. Jessica Darling's it list, 2013)
The day before seventh grade begins, twelve-year-old Jessica Darling gets a list from her sister, whose popularity and beauty made her a junior-high standout, but when she tries to follow it, all goes awry, including losing her best friend.